Entrepreneurial Orientation in Small Business Enterprises: Conceptualizations, Instrumentation and Research Guide - Linus Osuagwu (Sekolah Tinggi Manajemen IPMI, 2022)
The paper presents some conceptualizations of the entrepreneurial orientation construct, and presents a research instrument that may guide future research efforts in small business enterprises (SBEs). Materials in relevant extant literature and cognate experience were used to conceptualize entrepreneurial orientation and its various dimensions, in addition to a research instrument that may guide cognate future research of the entrepreneurial orientation construct in small business enterprises. The paper reports that there is equivocation in relevant extant literature regarding the entrepreneurial orientation construct with respect to its conceptualizations and dimensions in different business types and contextual settings. In addition, the paper proposes a research agenda for investigation of the entrepreneurial orientation construct in small business enterprises, especially in emerging economies in sub-Saharan Africa, Asia Pacific, South America, Middle East, and South East Asia, among others, with relatively underrepresented relevant research streams of the construct. The paper has theoretical and practical forms of values with regard to the entrepreneurial orientation construct in the domain of small business enterprises, especially when situated along other cognate management and entrepreneurship orientation constructs in different cultural and business contexts.